2009
DOI: 10.1002/eji.200839313
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of phospholipase C‐γ2 (PLCγ2) for Dectin‐1‐induced antigen presentation and induction of TH1/TH17 polarization

Abstract: DC recognize microbial components through an array of receptors known as PRR. PRR initiate intracellular signals, which engender DC with the capacity to stimulate T-cell responses. Dectin-1 is a PRR that recognizes b-glucan, a major constituent of many fungi's outer cell wall. Here we show that Dectin-1 activates DC through phospholipase (PLC)c2 signaling. PLCc2-deficient DC were unable to expand antigen-specific T cells and induce T H 1 and T H 17 differentiation in response to b-glucan. Mechanistically, PLCc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 49 publications
4
43
0
Order By: Relevance
“…The list of the significantly up-regulated genes in RBL-2H3 cells overexpressing Dectin-1 WT after 2 h of curdlan stimulation is shown in Table 1. Consistent with previous studies in macrophages and DCs, gene expressions of TNF-␣ (12, 13, 15), IL-4/IL-13 (38,39), early growth response transcription factor 3 (40,41), and suppressor of cytokine signaling 1 (42) were also up-regulated in curdlan-stimulated mast cells. Interestingly, curdlan did not stimulate gene expressions that were previously reported in macrophages and DCs, such as IL-1␤ (43, 44), IL-2 (18), [18][19][20], and IL-12 (18,20).…”
Section: Curdlan Stimulates the Expression Of Characteristic Genes Insupporting
confidence: 90%
“…The list of the significantly up-regulated genes in RBL-2H3 cells overexpressing Dectin-1 WT after 2 h of curdlan stimulation is shown in Table 1. Consistent with previous studies in macrophages and DCs, gene expressions of TNF-␣ (12, 13, 15), IL-4/IL-13 (38,39), early growth response transcription factor 3 (40,41), and suppressor of cytokine signaling 1 (42) were also up-regulated in curdlan-stimulated mast cells. Interestingly, curdlan did not stimulate gene expressions that were previously reported in macrophages and DCs, such as IL-1␤ (43, 44), IL-2 (18), [18][19][20], and IL-12 (18,20).…”
Section: Curdlan Stimulates the Expression Of Characteristic Genes Insupporting
confidence: 90%
“…The Egrs were rapidly induced, direct targets of Mincle triggering, as shown by CHX-blockade experiments. Several reports have indicated that Egr family members are induced by Dectin-1 ligands in macrophages and DCs (34,58) or neutrophils (59) in a calcineurin/NF-AT-dependent manner, which is likely also the case after Mincle stimulation. Although there are a number of reports on genes regulated by EGR family members in innate immune cells (60)(61)(62), the direct targets of EGRs in macrophages and DCs, especially in response to CLR activation, are currently unknown.…”
Section: Discussionmentioning
confidence: 95%
“…NFAT was linked to IL-2 release upon microbial challenge (15,27,29,30). Therefore, we asked whether NFAT also regulates IL-2 secretion in response to sterile stimuli, such as alum.…”
Section: Alum and Other Sterile Particulates Trigger Il-2 Release Fromentioning
confidence: 99%